2017
DOI: 10.1186/s13054-017-1784-0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring in the ICU: clinical considerations and consensus

Abstract: Glucose management in intensive care unit (ICU) patients has been a matter of debate for almost two decades. Compared to intermittent monitoring systems, continuous glucose monitoring (CGM) can offer benefit in the prevention of severe hyperglycemia and hypoglycemia by enabling insulin infusions to be adjusted more rapidly and potentially more accurately because trends in glucose concentrations can be more readily identified. Increasingly, it is apparent that a single glucose target/range may not be optimal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 64 publications
2
77
0
3
Order By: Relevance
“…Advances in continuous glucose monitoring (CGM) technology will further enable intense surveillance for early GV in managing patients with sepsis. We suggest that more studies are needed to investigate the optimal glucose control strategy in CGM for patients with high GV [29].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in continuous glucose monitoring (CGM) technology will further enable intense surveillance for early GV in managing patients with sepsis. We suggest that more studies are needed to investigate the optimal glucose control strategy in CGM for patients with high GV [29].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the system requires that a probe be inserted into a vein and connected to a pump, lines, and the glucose sensor, and thus is unsuitable for users during physical activity. Therefore, intravenous microdialysis has limited applications, such as glucose monitoring for patients assigned to bed rest in an intensive care unit . Even though they are popular and well established, invasive approaches involving a finger‐prick, surgery, and probe insertion are associated with pain and stress to their users.…”
Section: Invasive Biofluid‐based Glucose Monitoring Devicesmentioning
confidence: 99%
“…Real-time continuous glucose monitoring (CGM) provides frequent measurements of interstitial glucose levels, as well as direction and magnitude of glucose trends, which may have an advantage over POC glucose testing in detecting and reducing the incidence of hypoglycemia in the hospital setting (28,29). Several inpatient studies have shown that CGM use did not improve glucose control but detected a greater number of hypoglycemic events than POC testing (30,31). However, a recent review has recommended against using CGM in adults in a hospital setting until more safety and efficacy data become available (30) In most instances in the hospital setting, insulin is the preferred treatment for hyperglycemia (2).…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%